Anti-Müllerian hormone, follicle stimulating hormone, antral follicle count, and risk of menopause within 5 years. (August 2017) - Kim, Catherine; Slaughter, James C.; Wang, Erica T.; Appiah, Duke; Schreiner, Pamela; Leader, Benjamin; Calderon-Margalit, Ronit; Sternfeld, Barbara; Siscovick, David; Wellons, Melissa
Highlights: We evaluated the ability of several measures of ovarian age to predict the onset of menopause among women aged 45-49 years. About 60% with undetectable AMH underwent menopause in < 5 years. About 1/3 with <1 AFC underwent menopause in < 5 years. FSH had a non-linear relationship with the likelihood of menopause. Abstract: Objective: To evaluate the ability of concentration of anti-Müllerian hormone (AMH), antral follicle count (AFC), and concentration of follicle stimulating hormone (FSH) to predict the onset of menopause. Study design: The Coronary Artery Risk Development in Young Adults Study (CARDIA) Women's Study was an ancillary study to CARDIA, a population-based study of adults aged 18–30 years followed for 3 decades. For this report, participants were women (n = 426) who had attended the CARDIA year 15–16 (2000–2001) examination, had at least one ovary, were not pregnant, and underwent serum AMH and FSH measurement and transvaginal ultrasonography in 2002–2003. Main outcome measures: The probability of menopause in 5 years based upon AMH, FSH, and AFC. Results: The mean age of the women at the time of AMH, FSH, and AFC assessment was 43 years. The cumulative incidence of menopause at 25 years (or follow-up) was 27% ( n = 426), and the incidence within 5 years was 13% ( n = 55). Among women aged 45–49 years, undetectable AMH concentrations were associated with a greater than 60% probability of menopause within 5 years, whereas approximately 1/3 of women with no or just one antral follicle experienced menopause within 5 years. Both low and high concentrations of FSH were associated with greater odds of menopause than intermediate concentrations. Models with multiple markers did not improve the prediction of menopause over that afforded by models with single markers. Conclusion: The ability to predict onset of menopause was improved with any of the three menopausal markers in addition to age. AMH concentrations were more closely associated with menopause than AFC or FSH.